Análise polinica de argilas de Lagoa Negra - Pais, João (2010)
Palynological analysis of black shales from Lagoa Negra (Cantanhede) shows the presence of Cathaya and Keteleeria, Myrica and Engelhardtia being scarce. Comparison with other localities suggest an Upper Pliocene or Lower Pleistocene age for this association.